ANALISIS KEMANTAPAN JALAN METODE IRI MENGGUNAKAN APLIKASI ROADBUMP PRO & QGIS PADA JALAN DESA TANJUNG LUBUK – DESA PULAU GEMANTUNG ULU KABUPATEN OKI - Febriyadi; Zulkarnain, Yules Pramona; Sucika (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
On the Tanjung Lubuk Road to Pulau Gemantung Ulu Village, it is a road that connects the OKI Regency and OKU Regency roads which are very important access for the smooth running of the economy. Therefore, it is necessary to pay attention to the infrastructure of the connecting traffic road, in order to create better economic, social, cultural and educational growth. The method in this study uses road stability analysis with the IRI method and the Roadbump pro application which is applied to the Tanjung Lubuk village road - Pulau Gemantung Ulu Village, Tanjung Lubuk District, Ogan Komering Ilir Regency with three types of vehicles, namely sedans, SUVs, pick-ups. Furthermore, the data obtained is validated using the QGIS application to be more accurate. The results of the study show a comparison between the types of Kijang Innova SUV vehicles in 2016, Cary Sedans in 2005 and Hilux Pick-Ups in 2014. The comparison of years and types of vehicles greatly affects the IRI value in the Roadbump Pro Application. The results of the digitization of road stability mapping using the QGIS Application taken from the IRI value results on the Roadbump pro Application on the 6 km Tanjung Lubuk District Road section have been accurate and appropriate where there are 3 criteria, namely green indicates good road conditions, yellow indicates moderate road conditions and red indicates damaged road conditions.